2005
DOI: 10.1128/jvi.79.14.9180-9191.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Immunodeficiency Virus Type 1 Gene Expression by Clade-Specific Tat Proteins

Abstract: The major group of human immunodeficiency virus type 1 (HIV-1) strains that comprise the current global pandemic have diversified during their worldwide spread into at least 10 distinct subtypes, or clades. Subtype C predominates in sub-Saharan Africa and is responsible for the majority of worldwide HIV-1 infections, subtype B predominates in North America and Europe, and subtype E is prevalent in Southeast Asia. Significant amino acid variations have been observed among the clade-specific Tat proteins. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 79 publications
9
45
0
Order By: Relevance
“…We also observed that at all concentrations tested, there was no significant difference between the three variants except at 400 nM, the highest concentration tested where both subtype C Tat proteins had a higher activity (data not shown). This difference agrees with previously published data using different cell lines (28,44,57,66 (Fig. 1B) and Tat 96Bw (data not shown) elicited a transient increase in [Ca 2ϩ ] i in monocytes that returned to baseline 1 minute after the initial flux.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We also observed that at all concentrations tested, there was no significant difference between the three variants except at 400 nM, the highest concentration tested where both subtype C Tat proteins had a higher activity (data not shown). This difference agrees with previously published data using different cell lines (28,44,57,66 (Fig. 1B) and Tat 96Bw (data not shown) elicited a transient increase in [Ca 2ϩ ] i in monocytes that returned to baseline 1 minute after the initial flux.…”
Section: Resultssupporting
confidence: 82%
“…However, recent research has shown that the different genetic subtypes and recombinant forms of HIV-1 have biological differences with respect to transmission, replication, and disease progression (14,47,74,85). Moreover, different subtypes of Tat have different in vitro effects (17,18,27,28,57,62,66,67,76).…”
mentioning
confidence: 99%
“…However, in this trans-activation model, Tat is added as an exogenous protein that must traverse the cell membrane before it can bind the trans-activation responsive element and trans-activate HIV-1 long terminal repeat gene expression. A study using endogenously produced Tat showed that clade C Tat displayed higher affinities for both the trans-activation responsive element and for the positive transcription elongation factor b complex than clade B Tat and displayed a greater trans-activation potential (23). A recent study showed that the serine residues in Tat are phosphorylated by a cyclin-dependent kinase-2 mechanism and that this phosphorylation is important for HIV-1 transcription and the activation of integrated HIV-1 provirus (47).…”
Section: Discussionmentioning
confidence: 99%
“…Tat 93In is typical of clade C isolated, in that it possesses a C31S substitution in the cysteine-rich region (28). Of the seven highly conserved cysteines in Tat, only substitutions of Cys 31 do not affect its trans-activational ability (21,23,24,29).…”
Section: Tat Induces Il-10 In a Time-and Dose-dependent Manner Inmentioning
confidence: 99%
See 1 more Smart Citation